Factors Affecting Mothers’ Self Efficacy and Breastfeeding Practices - Farida Habib; Areeb AlBarqawi; Hala Saied; Haya AlFozan (GLOBAL HEALTH SCIENCE GROUP, 2021)
There are several factors affecting mother’s breastfeeding practices. These factors will lead to increased breastfeeding rates. The aim of this study was to assess the factors affecting mothers' breastfeeding practices and self-efficacy. Approximately 250 women participated in this study chosen through convenient sampling. The participants were recruited from paediatric outpatient clinics. Data collection tool consisted of 4 parts: Demographic data, obstetric data, factors affecting mothers' practices of infant feeding and Breastfeeding Self-efficacy Questionnaire. The mean age of the women was 30.78 + 5.62 years old and almost all of them (99.2%) were married. More than half (59.6%) of the participants completed their university education and 72% were working. The most influential environmental and social factors were attending the educational class before delivery (53.2%) and job condition (28.4%), short maternity leave (18.8%), and lack of privacy in public places (17.2%). Frustration over the baby refuse breastfeeding (20.8%) was the most influential emotional factor. About half of the mother’s (55.6%) had a high level of self-efficacy which was negatively correlated with breastfeeding emotional factors. It is concluded that working mothers needs more support and longer maternity leaves. Moreover, health care providers should offer educational class in accordance with the mother's needs.